The implementation of project-based learning in increasing speaking achievement and self-confidence - Jaya, Aswadi; Hermansyah, Hermansyah; Rosmiyati, Evi (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2019)
This study was to find out: 1) whether or not Project-based Learning (PBL) could make a significant difference in increasing both students‟ speaking achievement and self-confidence, and 2) the contribution of PBL towards both students’ speaking achievement and self-confidence. Out of 72 students, 40-average levels of achievement students were randomly selected as sample. These students were equally divided into two groups. The first group was taught using PBL and the second was given no treatment. For collecting the data, both groups were given a speaking test and self-confidence questionnaire. Both data were analyzed by using t-test to see the differences of speaking achievements and their self-confidence. Regression analysis was done to understand the contribution of PBL to the variables in the questions. The results showed that 1) there was a significant difference both in speaking achievement and self-confidence of the experimental group after being taught using PBL, 2) there was also a significant difference between experimental and control groups both in speaking ability and self- confidence, and 3) the contribution of PBL to the students’ speaking achievement was 99.7% and to self-confidence was 92.7%. In conclusion, PBL could be considered as an effective method in teaching speaking and in increasing students’ self- confidence.